К ВОПРОСУ О ПОЗИЦИОНИРОВАНИИ РУССКОГО ЯЗЫКА КАК ИНОСТРАННОГО НА РУБЕЖЕ ВЕКОВ И ТЫСЯЧЕЛЕТИЙ - Markūnas, Antoni (Studia Rossica Posnaniensia, 2008)
In this crucial period important changes in social and individual life have been observed. Political and economic transformation has affected the sphere of education, including foreign language teaching. Russian language undergoes distinct changes as well. In Poland nowadays it is returning to schools of different kind, especially to those of university level.